Effectiveness of the Ilizarov method in treating complex nonunions of the lower limb long bones - Ahmed Ibrahim Berzenji; Dedawan Namiq Rasul; Abdulkadr Muhammed S Alany (Journal of International Medical Research)
Background Complex nonunions of the lower limb long bones represent a challenging issue in orthopedics. Although the Ilizarov method is considered a successful treatment modality, its success varies with complications and patient-related factors. Objective This study aimed to evaluate the radiological and functional outcomes of the Ilizarov method in the management of complex nonunions of long bones. Specifically, we assessed bone healing, functional restoration, complication rates, and effectiveness of staged management strategies, including infection control and limb reconstruction. Methods This retrospective/prospective case series included 30 patients (31 nonunion cases) treated at three tertiary centers in Erbil city between 2020 and 2024. The patients underwent Ilizarov frame application following debridement and staged management for infection and bone transport. Outcomes were assessed using the Association for the Study and Application of the Method of Ilizarov criteria. Results The union rate of the study cohort was 90.3%, with a mean treatment duration of 9.26 months. Functional outcomes were rated as excellent, good, and poor in 67.7%, 22.6%, and 6.5% of the cases, respectively. Common problems included pin tract infections (35.5%), limb length discrepancy (32.3%), and malalignment (9.7%). Conclusion Although the Ilizarov method yielded high union rates and satisfactory functional outcomes in complex nonunions, limb length discrepancies and pin tract infections remain critical issues. Optimizing rehabilitation, compliance, and surgical planning is crucial for improving long-term functional outcomes.